An ultrawideband inverted double discone antenna with 150:1 impedance bandwidth. Issue 1 (January 2016) - Shahid, Irfan; Hussain, Fawad; Burki, Jehanzeb; Arif, M. Shoaib
ABSTRACT: In this article, an improved design of ultrawideband (UWB) inverted double discone (IDD) antenna is presented. Conventionally, IDD antennas are designed using tapered cylindrical wires as antenna elements. The tapering makes these antennas very fragile and the antennas suffer frequent damage during installation, transportation or even, due to perching of birds during normal operation. In this work, curved metal sheets are used instead of tapered wires to improve antenna robustness with no compromise on antenna's performance. Using this approach, an IDD antenna with an ultrawide impedance bandwidth is designed, fabricated, and tested. The measurements show good conformance with design and the measured antenna demonstrates an impedance bandwidth (for VSWR < 2) of 150:1 in frequency range of 120 MHz–18 GHz with omnidirectional radiation characteristics. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:181–184, 2016